2019
DOI: 10.1111/cas.14083
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine‐rich protein 61 regulates the chemosensitivity of chronic myeloid leukemia to imatinib mesylate through the nuclear factor kappa B/Bcl‐2 pathway

Abstract: Although the targeted tyrosine kinase inhibitor imatinib mesylate (IM) has achieved significant responses against CML in the clinical setting, a small proportion of patients fail to respond to IM treatment and their disease continues to progress, indicating resistance to IM therapy. As a secreted extracellular matrix protein, cysteine‐rich protein 61 (Cyr61) plays an important role in the resistance of solid tumors to chemotherapy, but its role in CML is unclear. In the present study, we observed that Cyr61 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 48 publications
(90 reference statements)
0
22
0
Order By: Relevance
“…Cysteine-rich protein 61 (Cyr61/CCN1) is a member of the CCN (Cyr61/CTGF/NOV) family and can regulate the survival, adhesion, and migration of various normal cells 3 . Recently, accumulating evidence has revealed that Cyr61 is highly expressed and that the increased Cyr61 level mediates tumor cell growth and metastasis, as well as drug resistance, in cancers 4 - 10 . In CRC patients, high expression of Cyr61 is found in tumor tissues and serum and is related to tumor growth and metastasis and shorter survival times 11 - 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine-rich protein 61 (Cyr61/CCN1) is a member of the CCN (Cyr61/CTGF/NOV) family and can regulate the survival, adhesion, and migration of various normal cells 3 . Recently, accumulating evidence has revealed that Cyr61 is highly expressed and that the increased Cyr61 level mediates tumor cell growth and metastasis, as well as drug resistance, in cancers 4 - 10 . In CRC patients, high expression of Cyr61 is found in tumor tissues and serum and is related to tumor growth and metastasis and shorter survival times 11 - 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In (T- and B-) ALL and CML, CCN1 expression has been detected in cell lines, and increased CCN1 levels have been demonstrated in BM-derived mononuclear cells, BM aspirate supernatant, and plasma samples of ALL and CML patients (Cao et al 2019 ; Song et al 2019 ; Zhu et al 2016 ). In ALL, BM and plasma CCN1 levels correlate with the percentage of blasts (Zhu et al 2016 ).…”
Section: Other Ccn Protein Family Membersmentioning
confidence: 99%
“…In ALL, BM and plasma CCN1 levels correlate with the percentage of blasts (Zhu et al 2016 ). In both ALL and CML, CCN1 enhances leukemic cell survival in vitro by decreasing apoptosis through enhanced BCL2 expression via the NF-κB pathway (Song et al 2019 ; Zhu et al 2016 ). In ALL, AKT but not ERK1/2 affects in vitro NF-κB signaling by CCN1 (Zhu et al 2016 ), whereas in CML, AKT nor ERK1/2 are involved in in vitro NF-κB signaling by CCN1 (Song et al 2019 ).…”
Section: Other Ccn Protein Family Membersmentioning
confidence: 99%
See 2 more Smart Citations